Renal toxic disease in a cat - Santos, Alex dos; Flores, Mariana Martins (Brazilian Journal of Veterinary Pathology, 2021)
This 8-month-old, male, mixed breed domestic shorthaired cat had a recent history of acute apathy and anorexia. It remained under hospital care for two days, during which it did not produce any urine. On the second day of hospitalization, another cat from the same household was brought in with similar clinical signs. These cats did not have any history of recent ingestion of antibiotics or other medication. Furthermore, they did not have any street or yard access since they were kept in an apartment. Both cats died spontaneously after a brief hospitalization period.